Kajian Kebutuhan Kebijakan Dalam Penyelenggaraan Pelayanan Terpadu Di Stasiun Sudirman - Noviyanti, Noviyanti (Warta Penelitian Perhubungan, 2010)
At this time the faci.lih; polia; I integrated terminal and the Integrated Terminal functions as aterminal in accordance with the criteria of an integrated terminal at some airports in Indonesia likeJakarta (Bus Damri by plane), Surabaya (Bus Damri by plane), ]ogajakarta (Bus, Train by plane) isa positive thing for creating efficienci; in transport FerVi.ces there has been no uniformity/ standards ofboth design and aperation of terminal facilities such integrated.It should be no legal basis concerning the implementation and aperation of the 'terminal facilities'governing integrated aspects of design, complete facilities and aperations as well as entering 'terminalfacilities' integrated as an element of the master plan of transportation nodes (airports, ports, stationsand terminals) that guarantee the safety aspects, safety, health and accessibility applied uniformly.